Perhitungan Carbon Emissions Pesawat Berukuran Sedang Rute Bandara Internasional Surabaya ke Bandara Internasional Soekarno Hatta Jakarta - Imam Sonhaji (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2022)
The high growth of aviation certainly has an impact on the environment, carbon emissions from aviation can affect health and climate change. This study aims to determine the amount of carbon emission produced in this study. This study aims to determine the amount of Carbon Emission CO2 produced in-flight activity from Juanda International Airport, Surabaya to Soekarno Hatta International Airport, Jakarta. The method used is qualitative with the ICAO Carbon Emissions Calculator Methodology tool. The results showed that the Carbon Emission CO2 generated from flight activities on the route was an average of 72,29 Kg per passenger, while the total amount of Carbon Emission CO2 generated from flight activities from March 2019 to March 2020 averaged 24.351 Tons CO2 per month